Unique Characteristics of Student Protests in Pre-revolutionary Universities of the Ukrainian Dnieper Region during the 1860s - Петровський, Володимир; Семененко, Валерій (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2019)
The article deals with the analysis of complex and multifaceted processes in the student sphere of Kyiv, Kharkiv, and partially Novorossiysk universities. The piece explores the problems of students’ autonomy (Sunday’s Schools, mutual benefit funds, libraries etc.), considered dangerous by the Russian Imperial government from 1861-1862. It is underscored that the refusal of the reigning regime to indulge the liberal movements of this time caused this wave of student unrest. However, it is important to note that a significant portion of department curators and professors did not support the government’s actions. Special attention is paid to the insurgency of Polish students at the university of St. Volodymyr and the reaction of the others. The relations between the government and the Jewish students as well as the reasons for students’ displeasure regarding some professors’ pedagogical styles are addressed. It is possible to conclude that the control over students intensified, increasing preventive measures in the late 1860’s as a direct result of these student protests.